Ethics and Aesthetics of Translation Exploring the Work of Atxaga, Kundera and Semprun - Hulme, Harriet (UCL Press, 2018)
Ethics and Aesthetics of Translation engages with translation, in both theory and practice, as part of an interrogation of ethical as well as political thought in the work of three bilingual European authors: Bernardo Atxaga, Milan Kundera and Jorge Semprún. In approaching the work of these authors, the book draws upon the approaches to translation offered by Benjamin, Derrida, Ricœur and Deleuze to highlight a broad set of ethical questions, focused upon the limitations of the monolingual and the democratic possibilities of linguistic plurality; upon our innate desire to translate difference into similarity; and upon the ways in which translation responds to the challenges of individual and collective remembrance. Each chapter explores these interlingual but also intercultural, interrelational and interdisciplinary issues, mapping a journey of translation that begins in the impact of translation upon the work of each author, continues into moments of linguistic translation, untranslatability and mistranslation within their texts and ultimately becomes an exploration of social, political and affective (un)translatability. In these journeys, the creative and critical potential of translation emerges as a potent, often violent, but always illuminating, vision of the possibilities of differentiation and connection, generation and memory, in temporal, linguistic, cultural and political terms.